Female authors and their male detectives: the ideological contest in female-authored crime fiction : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in English at Massey University, Palmerston North, New Zealand - Redmond, Robert Stanley (Massey University, 2008)
In the nineteen-eighties a host of female detectives appeared in crime fiction authored by women. Ostensibly these detectives challenged hegemonic norms, but the consensus of opinion was that their appropriation of male values and adherence to conventional generic closures colluded with a gender system of male privilege. Academic interest in the work of female authors featuring male detectives was limited. Yet it can be argued that these texts could have the potential to disrupt the hegemonic order through the introduction, whether deliberately, or inadvertently, of a female counterpoint to the hegemony. The hypothesis I am advancing claims that the reconfiguration of male detectives in works authored by women avoids the visible contradictions of gender and genre that are characteristic of works featuring female detectives. However, through their use of disruptive performatives, these works allow scope for challenging normal gender practices—without damage to the genre. This hypothesis is tested by applying the performative theories of Judith Butler to a close reading of selected crime novels. Influenced by the theories of Austin, Lacan and Althusser, Butler’s concept of performativity claims that hegemonic notions of gender are a fiction. This discussion also uses Wayne Booth’s concept of the implied author as a means of distinguishing the performative agency of the text from that of the characters. Agatha Christie, P.D. James, and Donna Leon, each with their male detective heroes, come from different generations. A Butlerian reading illustrates their potential for disrupting gender norms. Of the three, however, only Donna Leon avoids the return to hegemonic control that is a feature of the genre. Christie’s women who have agency are inevitably eliminated, while conformist women are rewarded. James’s lead female character is never fully at ease in her professional role. When thrust into a leadership she proves herself to be competent, but not ready or desirous of the senior position. Instead her role is to mediate the transition of her junior, a male, to that position. Donna Leon is different. The moral and emotional content of her narratives suggests an implied author committed to ideological change. Her characters simultaneously renounce and collude with illusions of patriarchal authority, and could lay claim to be models for Butler’s notion of performative resistance.
Keywords: Gender in fiction; Crime novels; Gender norms; Crime fiction; Fields of Research::420000 Language and Culture::420200 Literature Studies::420220 Comparative literature studies